Development of Local Content Curriculum Based on Pesantren Tahfīẓ in Mts. Al-Fathimiyah Banjarwati - Hidayat, Taufiq (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2023)
MTs. Al-Fathimiyah is one of the madrasas in the north coast area of Lamongan which since its establishment has focused on the development of tahfīẓ al-Qur’ān. This research aims to describe the implementation concept of madrasah-based pesantren tahfīẓ and analyzing curriculum development management in MTs. Al-Fathimiyah. This research is descriptive-qualitative research with a phenomenological approach. The analysis of curriculum development research uses the Hilda Taba concept which consists of 1). Producing experimental units; 2). Testing of experimental units; 3). Revision and consolidation; 4). Development of a curriculum framework; 5). Implementation and dissemination. The results of the study provide conclusions: 1). MTs. Al-Fathimiyah is a madrasah based pesantren that integrates the Ministry of Religion curriculum with the pesantren curriculum. Whereas in the management of students, MTs. Al-Fathimiyah implemented boarding student management; 2). The concept of curriculum development in MTs. Al-Fathimiyah focused on developing tahfīẓ al-quran which is integrated with the pesantren curriculum. The development model uses an inductive model so that it is more open to the process of improvement and improvement every year.